Potential use in the evaluation of wool and animal fibres of a novel electronic characterizer - Quispe Peña, Edgar Carlos (2018)
A novel Fibre Electronic Characterizer (called Fiber EF) was developed and validated. In the development of the Fiber EF, mechanical, optical, electronic and computer components were used and assembled. For the calibration, validation and evaluation of the potential use in animal fibres samples of well-known diameter patterns were taken from tops of sheep, mohair, alpacas, as well as samples of fibre snippets of vicuñas and alpacas, which were measured before and after calibration with the Fiber EF, OFDA2000 in 100 mode and Laserscan. Snippets (n=299) of unwashed alpaca samples were also measured in the OFDA 2000 and in the Fiber EF under field conditions. The developed Fiber EF allows to process the images of fibres obtained by artificial vision technology, making more than 8000 measurements per sample in 30 seconds. The results are shown in a friendly graphical interface that is part of the proprietary software developed for the Fiber EF. The calibration for the conversion of pixels to microns was adjusted to linear regressions with correlation coefficients very close to 1. The results of the validation indicate that the Fiber EF has high precision and accuracy for the average fibre diameter (MDF) with ranges of tolerance within those required by IWTO and ASTM, in the case of sheep wool and mohair fibres, although a little low in the case of vicuña fibres. On the other hand, a correlation close to 1 was found for measurements obtained by OFDA 2000 and the CEF with respect to alpaca fibres for MDF and comfort factor, both in the case of laboratory and field use. Finally, in the evaluation of cashmere fibres it was found that the results are characteristic of this type of fibres. It is concluded that the CEF can be used in the evaluation of sheep wool and mohair and alpaca fibres with great precision and accuracy, and should carry out more evaluations for vicuña and cashmere fibres.